Distribution of Paragonimus heterotremus and its intermedia hosts in the Northwest region of Vietnam - Doanh, Pham Ngoc; Le, Nguyen Thi; The, Dang Tat (Academia Journal of Biology, 2015)
Distribution of Paragonimus heterotremus and its intermedia hosts in the Northwest region of Vietnam